(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
The study dealt with the study of the holy shrines in Al-Najaf and Karbala from a geometrical viewpoint, where the development of these thresholds has been studied historically, as well as the most important structural and architectural features of these thresholds and the work of the current expansions to cope with the increase in the volume of worshipers and visitors. The construction works were characterized by high quality and efficiency in terms of style Construction and selection of structural materials as well as the sustainability of construction. The volume of expenses disbursed to these works is not small and it comes in total donations from individuals or institutions from inside and outside Iraq. Through this study it becomes clear that the role of worship in the holy shrines grows and evolves over time to keep pace with the urban development and the increase in the size of the worshipers and visitors, and not to maintain their identity, size and traditional forms With some of the main features of the dome and the minaret remain unchanged.